2011
DOI: 10.1007/s00248-010-9793-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity in Solenopsis invicta and Solenopsis geminata Ant Colonies Characterized by 16S amplicon 454 Pyrosequencing

Abstract: Social insects harbor diverse assemblages of bacterial microbes, which may play a crucial role in the success or failure of biological invasions. The invasive fire ant Solenopsis invicta (Formicidae, Hymenoptera) is a model system for understanding the dynamics of invasive social insects and their biological control. However, little is known about microbes as biotic factors influencing the success or failure of ant invasions. This pilot study is the first attempt to characterize and compare microbial communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
180
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(192 citation statements)
references
References 50 publications
9
180
0
1
Order By: Relevance
“…This characteristic of their colonies could be evolved in the ants to reduce the effects of these bacteria by allowing uninfected queens to maintain the production of males in the nest. However, the opposite was observed to the ant Solenopsis, where Wolbachia infection was prevalent in monogynous colonies (Ishak et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This characteristic of their colonies could be evolved in the ants to reduce the effects of these bacteria by allowing uninfected queens to maintain the production of males in the nest. However, the opposite was observed to the ant Solenopsis, where Wolbachia infection was prevalent in monogynous colonies (Ishak et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…and are known to be present in a number of ant species (Funaro et al, 2011;Ishak et al, 2011;Sapountzis et al, 2015). However, previous studies (Funaro et al, 2011) have found that these bacteria are not always present in different subcastes within a single ant colony or different colonies from the same population, indicating that these microorganisms are not essential for the development of the host species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR amplification was performed using the primers Gray28F and Gray519r (Table 1) (31), and sequencing reactions utilized a Roche 454 FLX instrument (Roche, Indianapolis, IN) with Titanium reagents, titanium procedures, a one-step PCR, and a mixture of Hot Start and HotStar high-fidelity Taq polymerases. After sequencing, all failed sequence reads and low-quality sequence ends and tags were removed, and sequences were depleted of any nonbacterial ribosome sequences and chimeras using custom software (21), as has been described previously (1).…”
mentioning
confidence: 99%